PO 8492 Repeated artemisinin-based treatment on malaria sexual parasite distribution in population living in a malaria-endemic area of burkina faso. (24th April 2019) - Diarra, Amidou; Soulama, Issiaka; Nebie, Issa; Ouattara, Maurice; Kabore, Moise; Sombie, Benjain; Tiono, Alfred B; Ouedraogo, Alphonse; Sirima, Sodiomon B
Abstract : Background: Malaria elimination and its ultimate eradication will require drugs targeting all stages of the parasite's life cycle. Yet, very few drugs are known to be effective on the sexual stages (gametocytes) of Plasmodium falciparum . Artemisinin-based combination therapy (ACT) has been shown to have some early-stage gametocytocidal effects on in vitro and in feeding experiments. However, field studies showed that artesunate reduces but does not prevent post-treatment transmission of P. falciparum to mosquitos. Methods: 763 children and adult patients with acute uncomplicated Plasmodium sp. malaria were included in a phase IIIb/IV comparative, randomised, multi-centre, open label, parallel 3-arm clinical trial to assess safety and efficacy of repeated administration of pyronaridine-artesunate, dihydroartemisinin-piperaquine or artemether-lumefantrine or artesunate-amodiaquine over a two-year period. Drugs were given based on the body weight and volunteers were followed up for 42 days. Clinical signs and symptoms were recorded and filter paper and blood smears collected during each visit. Malaria parasites were assessed and parasite density development stages determined by light microscopy. Results: P. falciparum gametocyte was 1.9%, during the two years of follow-up. From the three treatment arms, artesunate-amodiaquine was the arm bearing more P. falciparum gametocyte with 68.7%, dihydroartemisinin-piperaquine accounted for 6.3% and pyronaridine-artesunate for 25%. P. falciparum gametocyte was more pronounced in populations having parasite density ≤1 00 000 parasites/µl compared to above parasitaemia. Conclusion: Repeated ACTs treatment didn't clear P. falciparum gametocyte in a population infected with uncomplicated malaria.